Farmer perspectives of the on-farm and off-farm pros and cons of planted multifunctional riparian margins. (February 2017) - Maseyk, Fleur J.F.; Dominati, Estelle J.; White, Toni; Mackay, Alec D.
Highlights: Multi-tier riparian margin plantings provide many benefits on and off-farm. Fenced only riparian margins also deliver benefits, but less than planted margins. Riparian margins are not a panacea but do contribute to multifunctional landscapes. Riparian margin plantings are an important ecological infrastructure investment. The costs associated with margin plantings should be considered in this context. Abstract: The planting of riparian margins is a policy option for pastoral farmers in response to land use induced environmental issues such as declining water quality, stream bank erosion, and loss of aquatic and terrestrial habitat. We elicited the views and experiences as to pros and cons of planting riparian margins from two sets of dairy farmers from Taranaki, New Zealand: those who are or have planted riparian margins, and those who have not yet done so. Those farmers who have planted riparian margins identified 21 positive aspects of riparian margin plantings and 11 negative aspects of riparian margin plantings. Perceived benefits identified by this group include water quality, increased biodiversity, the provision of cultural ecosystem services, immediate direct benefits to farm management and the farm system, and in some instances increased productivity on-farm. In contrast, those farmers that had fenced but not planted their riparian margins did not consider that riparian margin plantings could add further benefits to that which could be achieved by excluding stock from waterways, and associated only negative perceptions with riparian margin plantings. Planting riparian margins is not cost neutral and will not deliver anticipated environmental benefits in every situation. However, we argue that riparian margin plantings are an important ecological infrastructure investment that needs to be captured within a wider policy framework, the benefits of which extend beyond the mitigation of a single negative externality generated by land use practices, such as nutrient loss, and contribute to a multifunctional landscape.